Diagnostic and Therapeutic Consequences of Thyroid Ultrasound: A Retrospective Explorative Cohort Study using Claims Data - Warkentin, Lisette; Kühlein, Thomas; Tomandl, Johanna; Biermann, Valeria; Klemperer, David; Sutter, Katharina; Steffen, Jan; Schedlbauer, Angela; Hueber, Susann (Das Gesundheitswesen, 2025)
Ultrasound (US) screening for thyroid cancer and other non-indicated US of the thyroid lead to the detection of mostly benign nodules or small papillary carcinomas. Although US screening for thyroid cancer is discouraged by guidelines, it continues to be performed. We aimed to explore the effects of thyroid US early in the diagnostic process on further diagnostic and therapeutic procedures in Germany.In a retrospective observational cohort study, we analysed claims data from 2012 to 2016 of patients without history of thyroid disease. After propensity score matching for sociodemographic characteristics, a selection of symptoms and diagnoses (e. g. fatigue, hypertension) and morbidity in the last year, patients with an initial TSH test and a thyroid US within 28 days after the test were compared to patients receiving an initial TSH test but no early US. Patients with hypo- or hyperthyroidism diagnosed directly after the initial TSH were excluded. Thyroid-specific morbidity, follow-up tests and therapeutic pathways were analysed.In total, 5,390 patients remained in each group after data selection and matching (mean age: 46.5 years (SD=15.0), 58% female). Early US was associated with higher thyroid-specific morbidity, especially regarding thyroid nodules. Additionally, more patients in the observation group received thyroid-related follow-up test. The utilization of ambulatory healthcare services in the first year was higher in this group, especially for internal medicine working in general practice, internal medicine, nuclear medicine, and radiology.Early use of US was associated with increased thyroid-specific morbidity, even after excluding patients with hypo- or hyperthyroidism after the initial TSH. Subsequently more diagnostic and therapeutic procedures were performed. Increased morbidity may be due to overtesting with diagnostic cascades resulting in overdiagnosis and overtreatment. Further research is needed to estimate the true number of overdiagnoses.
Keywords: Schilddrüsenknoten; Überdiagnostik; Routinedaten